2021
DOI: 10.3390/microorganisms9071532
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution of Bacterioplankton Molecular Ecological Networks in the Yuan River under Different Human Activity Intensity

Abstract: Bacterioplankton communities play a crucial role in freshwater ecosystem functioning, but it is unknown how co-occurrence networks within these communities respond to human activity disturbances. This represents an important knowledge gap because changes in microbial networks could have implications for their functionality and vulnerability to future disturbances. Here, we compare the spatiotemporal and biogeographical patterns of bacterioplankton molecular ecological networks using high-throughput sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…When the stable environments in the upper reaches are disturbed by anthropogenic activity, niche-based selection strengthens and bacterioplankton communities become less characterized by stochasticity. Freshwater bacterioplankton can become exposed to lower physiological stress at low human activity intensity levels, and they can then grow and reproduce more freely, which results in the dominance of stochastic processes ( Wu B. et al, 2021 ). Jiao S. et al (2020) found that in low environmental stress ecosystems which experience lower environmental heterogeneity or under less competitive interactions between environmental generalists, stochastic assembly mechanisms can overrule deterministic processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the stable environments in the upper reaches are disturbed by anthropogenic activity, niche-based selection strengthens and bacterioplankton communities become less characterized by stochasticity. Freshwater bacterioplankton can become exposed to lower physiological stress at low human activity intensity levels, and they can then grow and reproduce more freely, which results in the dominance of stochastic processes ( Wu B. et al, 2021 ). Jiao S. et al (2020) found that in low environmental stress ecosystems which experience lower environmental heterogeneity or under less competitive interactions between environmental generalists, stochastic assembly mechanisms can overrule deterministic processes.…”
Section: Discussionmentioning
confidence: 99%
“…We then construct Bacterioplankton molecular ecological networks using 16S rRNA and molecular ecological network methods ( Deng et al, 2012 ; Jiao S. et al, 2020 ; Wu B. et al, 2021 ). Phyla-level network analysis was performed to identify the relations between microbial taxa using Cytoscape version 3.4.0 combined with the CONET plug-in 3 ( Jiao S. et al, 2020 ; Xia et al, 2020 ; Mishra et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there was a tight association among the major genera. Modules are groups of nodes that are well connected with one another, but less connected with nodes belonging to other modules [ 43 , 61 ]; nodes in the same module occupy similar ecological functions and niches [ 62 ]. Higher modularity indicated that the sediment bacterial community had more ecological niches and could maintain community stability through functional and ecological niche concentration, thus minimizing environmental impacts [ 63 ].…”
Section: Discussionmentioning
confidence: 99%